2004
DOI: 10.1007/s00446-003-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Condition-based consensus solvability: a hierarchy of conditions and efficient protocols

Abstract: The condition-based approach for consensus solvability consists of identifying sets of input vectors, called conditions, for which there exists an asynchronous protocol solving consensus despite the occurrence of up to f process crashes. This paper investigates C f , the largest set of conditions which allow us to solve the consensus problem in an asynchronous shared memory system.The first part of the paper shows that C f is made up of a hierarchy of classes of conditions, CWe prove that each one is strictly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Last but not the least, this section describes how FLP can be circumvented by weakening the very definition of consensus, i.e., by modifying it. Currently, we are aware of a single type of algorithm that fits in this category in the system model that we consider in the paper: algorithms based on the condition-based approach (Mostefaoui et al, 2003b(Mostefaoui et al, , 2004Friedman et al, 2002). For crash faults, there is also k-set consensus, which allows k different values to be decided (Chaudhuri, 1993).…”
Section: Modifying the Problemmentioning
confidence: 99%
“…Last but not the least, this section describes how FLP can be circumvented by weakening the very definition of consensus, i.e., by modifying it. Currently, we are aware of a single type of algorithm that fits in this category in the system model that we consider in the paper: algorithms based on the condition-based approach (Mostefaoui et al, 2003b(Mostefaoui et al, , 2004Friedman et al, 2002). For crash faults, there is also k-set consensus, which allows k different values to be decided (Chaudhuri, 1993).…”
Section: Modifying the Problemmentioning
confidence: 99%
“…• For values of d ≤ 0, for inputs in C consensus is solvable by more and more efficient protocols in a shared memory asynchronous system as we go from d = 0 to d = −t [40].…”
Section: The Combined Power Of Conditions and Information On Failuresmentioning
confidence: 99%
“…We use the results of [12], in which the requirements of the consensus problem are relaxed. The authors have identified conditions for which there exists an asynchronous protocol that solves the consensus problem despite the occurrence of t process crashes.…”
Section: Deployment In a Dynamic Networkmentioning
confidence: 99%
“…The only change concerns the designation of a representative host for each node of the hierarchy. We use the algorithm of [12] to elect such a representative and to build a common view of the placement of the components.…”
Section: Algorithmmentioning
confidence: 99%